2021
DOI: 10.1038/s41598-021-97109-6
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant and antibacterial insights into the leaves, leaf tea and medicinal roots from Astragalus membranaceus (Fisch.) Bge.

Abstract: Used as traditional Chinese medicine, Astragalus membranaceus (Fisch.) Bge. (A. membranaceus) roots are also used as tonic food material in a wide range of applications, while the leaves are left in the field, unused. Therefore, comprehensively exploring and utilizing the leaves will inevitably reduce the associated resource waste and environment pollution. In this study, the plant leaves were processed into tea using green tea processing technology. Bioactive components, antioxidant and antibacterial activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Extensive research studies have identified the antioxidant properties of A. membranaceus Fisch. ex Bunge ( Durazzo et al, 2021 ; Samuel et al, 2021 ), C. cassia L.) J. Presl ( Yang et al, 2012 ; Rao and Gan, 2014 ), and S. cuneata (Oliv.) Rehder and E.H. Wilson ( Zhang et al, 2021 ), displaying significant prevention from tissue injury via antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research studies have identified the antioxidant properties of A. membranaceus Fisch. ex Bunge ( Durazzo et al, 2021 ; Samuel et al, 2021 ), C. cassia L.) J. Presl ( Yang et al, 2012 ; Rao and Gan, 2014 ), and S. cuneata (Oliv.) Rehder and E.H. Wilson ( Zhang et al, 2021 ), displaying significant prevention from tissue injury via antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Rehder and E.H. Wilson, and Cinnamomum cassia (L.) J. Presl ( Table 1 ). Interestingly, antioxidant activity is common among all of these components ( Yang et al, 2012 ; Rao and Gan, 2014 ; Durazzo et al, 2021 ; Li et al, 2021 ; Samuel et al, 2021 ; Zhang et al, 2021 ; Xu et al, 2022 ). According to TCM theory, the combination of these five drugs work in concert to reduce inflammation, resist oxidation, and fight against aging by enriching Qi, eliminating phlegm and blood stasis, and promoting blood circulation; thereby suitable for the treatment of stroke, atherosclerosis, and other related cardiovascular and cerebrovascular conditions ( Liang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized clinical trials have demonstrated that Astragalus-based interventions can reduce cancer symptoms, improve the quality of life and immune function, increase plasma nerve growth factor levels, and slow the progression of chemotherapyinduced peripheral neuropathy [78,156]. Currently, Astragalus extracts or preparations [157] have been used in clinical trials for their antitumor effects on digestive, respiratory, epithelial tissue, and hematological malignancies (Table 3) [158][159][160].…”
Section: Clinical Trials On the Antitumor Effects Of Apsmentioning
confidence: 99%
“…It was shown that neither caffeic acid nor rosmarinic acid are present in the A. mongholicus raw material. Recent research indicates that the antiradical capacity of these raw material root extracts is attributed to the presence of polysaccharides and flavonoids [31][32][33][34].…”
Section: Astragalus Mongholicusmentioning
confidence: 99%